A Rare Case of Ixazomib-Induced Cutaneous Necrotizing Vasculitis in a Patient with Relapsed Myeloma - Heather Katz; Mina Shenouda; Deena Dahshan; George Sonnier; Yehuda Lebowicz (Case Reports in Hematology)
Ixazomib is the only oral proteasome inhibitor used in relapsed/refractory myeloma. Cutaneous side effects due to ixazomib have been documented in the literature; however, cutaneous necrotizing vasculitis is extremely rare. We describe a case of a 74-year-old man with relapsed multiple myeloma who was started on ixazomib, lenalidomide, and dexamethasone. He developed several skin lesions that were biopsied and revealed cutaneous necrotizing vasculitis. Ixazomib was held with resolution of the vasculitic lesions and restarted with dexamethasone to 20 mg on the day of treatment and 20 mg dose the day after treatment.